Intersectionality in informal care research: a scoping review. Issue 1 (February 2023) - Hengelaar, Aldiene H.; Wittenberg, Yvette; Kwekkeboom, Rick; Van Hartingsveldt, Margo; Verdonk, Petra
Aim: Informal caregivers share common experiences in providing care to someone with health and/or social needs, but at the same time their experiences differ across diverse backgrounds such as gender, age, culture, as these aspects of diversity co-shape these experiences. This scoping review aims to explore how aspects of diversity, across their intersections, are currently incorporated in informal care research and discusses how an intersectional perspective can further develop our understanding of informal care. Methods: A scoping review was performed to map relevant caregiving literature from an intersectionality perspective. Key terms 'informal care' and 'intersectionality' were used for a search in four databases resulting in the inclusion of 28 articles. All 28 studies were analysed based on a scoping review created intersectionality informed coding scheme. Results: Aspects of diversity are largely understudied in informal care research, in particular across their intersections and from a critical perspective. This intersectional informed analysis revealed that when studying diverse caregiving experiences the use of intersections of dimensions of diversity provides a nuanced understanding of these experiences. Conclusions: Adopting an intersectional perspective ensures that not only different categories or social identities of caregivers are included in future studies, but the mutual relationships between these categories embedded in their specific context are actually studied.